The Funeral of Mr. Wang Life, Death, and Ghosts in Urbanizing China - Kipnis, Andrew B. (University of California Press, 2021)
In rural China funerals are conducted locally, on village land by village elders. But in urban areas, people have neither land for burials nor elder relatives to conduct funerals. Chinese urbanization, which has increased drastically in recent decades, involves the creation of cemeteries, state-run funeral homes, and small private funerary businesses. The Funeral of Mr. Wang examines social change in urbanizing China through the lens of funerals, the funerary industry, and practices of memorialization. It analyzes changes in family life, patterns of urban sociality, transformations in economic relations, the politics of memorialization, and the echoes of these changes in beliefs about the dead and ghosts. "This book is highly original and addresses a topic of central importance to understanding Chinese family life and the limits of a party-state's regulatory power over the society and individual citizens. Original and systematic fieldwork is expertly used to illustrate core arguments. To my knowledge there is no competing ethnography." - Deborah Davis, Professor Emerita of Sociology, Yale University "The Funeral of Mr. Wang is a vivid portrait of how the transition from life to death is negotiated in the midst of a rapidly transforming urban Chinese society. Showing how death in contemporary China generates interconnected processes of cultural recombination among family members, funeral service providers, bureaucratic regulators, strangers, and ghosts, this book will be critical reading for all students of China and of death in contemporary societies." - David A. Palmer, coauthor of The Religious Question in Modern China